Weak solution for fractional p(x)-Laplacian problem with Dirichlet-type boundary condition - Sabri, A.; Jamea, A.; Alaoui, H. T. (Methods of Functional Analysis and Topology, 2020)
In the present paper, we prove the existence and uniqueness result of weak solutions to a class of fractional p(x)-Laplacian problem with Dirichlet-type boundary condition, the main tool used here is the varitional method combined with the theory of fractional Sobolev spaces with variable exponent. Для одного класу задач із дробовим p(x)-лапласіаном з граничною умовою типу Дирихле доведено теорему про існування та єдиність слабкого розв’язку. Використовуються варіаційний метод і теорія дробових просторів Соболева змінного порядку.